The Role of Artificial Intelligence in Achieving Sustainable Competitive Advantage: A Field study of a Number of private Schools in Baghdad (The International Journal for Scientific Research, 2025)
This study aims to explore the role of artificial intelligence in achieving sustainable competitive advantage within organizations. It relied on a descriptive-analytical approach. It also emphasized the importance of artificial intelligence as a strategic tool for enabling organizations to rapidly adapt, innovate, and make sound decisions based on data, customer behavior, and the understanding of their behavior. This reliance on artificial intelligence technologies can achieve long-term advantage. Private schools were selected, and the sample size was (100). These schools were distributed to a number of school principals, resulting in a total of (100) valid questionnaires for analysis. The SPSS program was used to extract descriptive statistical methods for testing hypotheses. Literature reviews and previous studies were also used. The study recommended the adoption of comprehensive strategies to integrate artificial intelligence with human resource training to achieve objectives.
Keywords: Artificial Intelligence; AI-based decision-making; Artificial Intelligence Strategy; sustainable competitive advantage